2021
DOI: 10.1128/iai.00031-21
|View full text |Cite
|
Sign up to set email alerts
|

Differential Outcome between BALB/c and C57BL/6 Mice after Escherichia coli O157:H7 Infection Is Associated with a Dissimilar Tolerance Mechanism

Abstract: Enterohemorrhagic Escherichia coli (EHEC) infections can result in a wide range of clinical presentations even though EHEC strain belongs to O157:H7 serotype, one of the most pathogenic ones. Although pathogen virulence influences disease outcome, we emphasize about the concept of host-pathogen interactions, which involve resistance or tolerance mechanisms in the host that finally determine host fitness and bacterial virulence. Taking advantage of the genetic differences between mouse strains, we analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Several pieces of evidence support that protection against non-invasive enteric infections such as cholera and enterotoxigenic Escherichia coli (ETEC) diarrhea is mainly mediated through antigen-specific secretory IgA (SIgA) antibodies produced locally in the mucosa (Czerkinsky and Holmgren, 2015). Similarly, we recently demonstrated that protection against HUS associated with STEC-infection in mice is dependent on the B cell response and IgA specific antibodyresponse in the intestine (Bernal et al, 2021).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Several pieces of evidence support that protection against non-invasive enteric infections such as cholera and enterotoxigenic Escherichia coli (ETEC) diarrhea is mainly mediated through antigen-specific secretory IgA (SIgA) antibodies produced locally in the mucosa (Czerkinsky and Holmgren, 2015). Similarly, we recently demonstrated that protection against HUS associated with STEC-infection in mice is dependent on the B cell response and IgA specific antibodyresponse in the intestine (Bernal et al, 2021).…”
Section: Methodsmentioning
confidence: 92%
“…Control and FliC or H7-immunized mice were euthanized at day 6 p.i. with 125/99 pW strain to determine intestinal colonization as previously described ( Bernal et al., 2021 ). Briefly, 5 cm of the small and large intestine and the cecum were excised.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As to several mucosal pathogens, it has been reported that pathogen-specific IgA can prevent infection 31 , 41 45 . As to Stx, previous studies indicated that mucosal vaccination could prevent disease and induce production of toxin-specific IgA antibodies, however, the effect of passively administered Stx-specific IgA was not clarified 33 , 39 , 46 . To examine the therapeutic effects of the plant-based IgA on oral administration, a sufficient amount of plantibody needs to be produced.…”
Section: Discussionmentioning
confidence: 99%
“…S3). In a previous study, both C57BL/6 and BALB/c mice were infected with E. coli , while C57BL/6 showed increased intestinal damage, altered integrity of the intestinal barrier, and impaired renal function that resulted in increased mortality ( 38 ). This phenomenon implies that it would be easier to observe BLP-induced tolerance in C57BL/6J mice than in other breeds.…”
Section: Discussionmentioning
confidence: 99%